A colour atlas and text of clinical medicine - Forbes, C. D.; Jackson, William F. (Wolfe, 1993)
Covering the whole of clinical medicine, this work comprises illustrations highlighting the clinical signs of all major medical disorders, accompanied by radiological, ultrasound, endoscopic and other images. Each chapter provides a guide to symptoms, investigations, common and rare disorders
Keywords: Clinical medicine -- Clinical Medicine